Improved Health-Related Quality of Life in Older Kidney Recipients 1 Year After Transplantation - Lønning, Kjersti (Transplant Direct, 2018)
BACKGROUND: We aimed to evaluate changes in health-related quality of life (HRQoL) in patients 65 years or older from time of kidney transplantation (KTx) until 1 year postengraftment. METHODS: A single-center prospective study was conducted. HRQoL was measured pre-KTx and at 2, 6, and 12 months postengraftment using self-reported Kidney Disease and Quality of Life short-form version 1.3. Intraindividual scores before and after KTx were evaluated. Liu Comorbidity Index was registered at enlisting. short-form-36 scores were additionally compared with scores from an age-matched population. RESULTS: From January 1, 2013, until November 30, 2016, a total of 289 waitlisted patients were included. By September 1, 2017, 134 had reached 1 year postengraftment, and valid questionnaires were available in 120 (90%) patients. Mean age at KTx was 71.6 years (±4.3 years), 71% were male. Living donor was used in 21%, and preemptive KTx was performed in 30% of the recipients. Median waiting time for KTx from deceased donor was 16 months (range, 0.6-50.5 months). A total of 79 (66%) recipients had a Liu Comorbidity Index score of 3 or less. All HRQoL scores except the domain social function improved at 2 months postengraftment and remained stable or continued to improve at 1 year. HRQoL scores 12 months postengraftment were similar to those described in an age-matched general population except for the domain social function which remained at a significantly lower level. Time in dialysis was the most important variable associated with impaired HRQoL postengraftment. CONCLUSIONS: HRQoL scores showed clinically significant improvement in older KTx recipients 1 year posttransplant.